A Descriptive study on the knowledge of caregivers on the emergency management of traumatic dental injuries of individuals with intellectual disabilities - Salvatierra, Kriza Nikka C.; Tiongson, Deanne Paulene S. (Department of Community Dentistry, University of the Philippines Manila, 2017)
INTRODUCTION: Individual with intellectual disability (IID) are inflicted with difficulties such as seizures,poor motor coordination, poor muscular control, decreased defensive reflexes and other self-injurious behavior. This is why Traumatic dental injuries (TDIs) are the most commonly occuring incidence of trauma to individuals with intellectual disability (Glendor 2008). These individuals are dependent of the care they receive from others. The term "caregiver" stands for the people who give care and/or look after them. These people include parents, relatives, teacher/s, and/or nannies that as the term suggests, cater to the welfare of these individuals. This study is an attempt to determine the knowledge of caregivers of individuals with intellectual disability regarding traumatic dental injuries in three special education schools in Metro Manila.